Exploring the heterogeneity in depression through value attached to agency and communion - Rana B. Kalkan-Cengiz; Laura Sels; Martine W. F. T. Verhees; Peter Kuppens (PLoS ONE, 2025)
Depression is a heterogeneous disorder with varying expressions and underlying factors. This study adopted an interpersonal perspective, examining how individual differences in the value attached to agency (getting ahead) and communion (getting along) explain variability in depressive experiences. Specifically, we explored whether these individual differences explain what kind of situations can feed into depression and whether, together with the frustration of these dimensions, they can help explain the heterogeneity in types of depressive experience, behaviors, and symptoms. In this preregistered study, 510 participants prescreened for depressive symptoms reported negative affect in response to vignettes depicting agentic and communal frustration, and completed questionnaires on value attached to and frustration of agency and communion, types of depressive experiences, behaviors, and depressive symptoms. The results suggested that valuing agency and communion appears to increase individuals’ susceptibility to situations that frustrate their agentic and communal motives, respectively, although the context in which these frustrations occurred played a key role. However, at the trait level, it was overall frustration of these motives, not the value attached to them or their interaction, that was associated with depression. If anything, strongly valuing agency and communion may instead reflect adaptive psychological profiles as they showed some buffering effects. Moreover, agentic and communal frustration were overall not differentially related to different manifestations of depression, and may reflect a general frustration of motives or general negativity.